2014
DOI: 10.1155/2014/734068
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Posttranscriptional Regulations of theHLA-GGene

Abstract: HLA-G has a relevant role in immune response regulation. The overall structure of the HLA-G coding region has been maintained during the evolution process, in which most of its variable sites are synonymous mutations or coincide with introns, preserving major functional HLA-G properties. The HLA-G promoter region is different from the classical class I promoters, mainly because (i) it lacks regulatory responsive elements for IFN-γ and NF-κB, (ii) the proximal promoter region (within 200 bases from the first tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
181
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(192 citation statements)
references
References 159 publications
(253 reference statements)
7
181
0
4
Order By: Relevance
“…We found that HLA-G was lower in all cell lines, which was consistent with previous studies [40]. Previous researches have demonstrated that HLA-G expression in ovarian cancer and melanoma decreased or even completely disappeared after long-term culture of fresh HLA-G positive tumor cells in vitro [57-60], suggesting that the expression of HLA-G in tumor cells is regulated by the tumor microenvironment [61]. In addition, by using flow cytometry, we found that tumor-infiltrating NK cells were mainly expressed in ILT2.…”
Section: Discussionsupporting
confidence: 91%
“…We found that HLA-G was lower in all cell lines, which was consistent with previous studies [40]. Previous researches have demonstrated that HLA-G expression in ovarian cancer and melanoma decreased or even completely disappeared after long-term culture of fresh HLA-G positive tumor cells in vitro [57-60], suggesting that the expression of HLA-G in tumor cells is regulated by the tumor microenvironment [61]. In addition, by using flow cytometry, we found that tumor-infiltrating NK cells were mainly expressed in ILT2.…”
Section: Discussionsupporting
confidence: 91%
“…Both modules are divergent in HLA-G, rendering the HLA-G 5′URR unique among HLA genes. 29,39 The known regulatory elements of HLA-G present distinctive structural characteristics and extend up to~1500-bp upstream of the first translated codon, instead of only 500 bp in other class I genes. These unusual features may be responsible for the non-classical transcriptional regulation of HLA-G and its restricted expression in specific tissues such as the trophoblast or thymic epithelial cells in nonpathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The LCR region is critical for the HLA-G expression regarding when and where it should be expressed. 29 The extent of the region explored in previous and present sequencing surveys is represented by a gray bar for each study. (b) Nucleotide sequence variations identified in the previous and present sequencing surveys.…”
Section: Population Genetic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription processes regulating MHC gene expression were broadly investigated (8), and a few posttranscription regulators were discovered as well (9,10). However, whether RNAbinding proteins (RBPs) control the expression of classical and nonclassical MHC class I proteins is largely unexplored.…”
mentioning
confidence: 99%